971. Online Medical Education Improves Knowledge of Data on Appropriate and Timely Use of Influenza Antiviral Medications to Patients at High Risk for Influenza-Related Complications and Morbidity. (4th December 2021) - Armagan, Allison; Smith, Roderick
Abstract: Background: Many patients are at a higher risk of influenza complications because of age and comorbidities. We sought to assess whether online education, focused on appropriate and timely use of influenza antiviral medications to patients at high risk for influenza-related complications and morbidity, could improve knowledge, competence, and confidence of clinicians. Methods: Primary care physicians (PCPs) and pediatricians participated in a 30-minute video lecture with synchronized slides. Educational effect was assessed using a repeated-pairs design with pre-/post-assessment. Three multiple choice questions assessed knowledge/competence, and 1 question assessed confidence. Statistical tests to assess significance: Paired samples t-test for overall average number of correct responses and for confidence rating; McNemar's test for individual questions (5% significance level, P < .05). Cohen's d estimated the effect size impact on number of correct responses (< .20 modest, .20-.49 small, .59-.79 moderate, ≥.80 large). Data were collected from 10/28/20 to 12/23/20. Results: Average knowledge/competence improved from 29% to 43% (N=430, P< .001, Cohen's d = 0.46) among primary care physicians and from 31% to 43% (N=226, P< .001, Cohen's d = 0.38) among pediatricians. Post participation, 12% more PCPs and pediatricians answered all questions correctly. Relative improvements post-participation in specific areas were as follows (P< .001): (i) 105% improvement among PCPs and 100% improvement among pediatricians in findings associated with the efficacy of treatment with antivirals for influenza in hospitalized patients. (ii) 117% improvement among PCPs and 104% improvement among pediatricians in identifying the antiviral with the greatest activity against influenza B viral strain as reported in a phase 3 clinical trial. (iii) 34% of PCPs and 46% of pediatricians had a measurable improvement in confidence after completing the program. Conclusion: This study demonstrated the success of a video lecture with synchronized slides at improving PCPs and pediatricians knowledge, competence and confidence related to appropriate and timely use of influenza antiviral medications to patients at high risk for influenza-related complications and morbidity. Disclosures: All Authors : No reported disclosures